Comparative evaluation of the oxidation resistance of untreated, annealed and quenched 434 ferritic stainless steels in corrosive electrolytes. Issue 1 (31st December 2022) - Loto, Roland Tolulope
Abstract: The corrosion resilience of untreated, annealed and quenched 434 ferritic stainless steel (434FS) was studied in 1 M H2 SO4 media at 0–1.75% NaCl concentration. Without the chlorides, annealed 434FS depicted the maximal corrosion rate output of 21.39 mm/y in comparison with 13.60 mm/y and 13.10 mm/y for the untreated and quenched 434FS. At 0.25% NaCl concentration, a significant decrease in the corrosion of untreated 434FS was observed (3.22 mm/y), which increased progressively with an increase in NaCl concentration till 15.44 mm/y (1.75% NaCl). Corrosion of annealed 434FS decreased to 15.37 (0.25% NaCl) and 8.44 mm/y (1.75% NaCl). Corrosion of quenched 434FS increased to 17.82 mm/y before decreasing to 8.93 mm/y at 1.75% NaCl concentration. The steels exhibited significant metastable pitting behaviour. However, the potential for metastable pitting activity decreased significantly for annealed and quenched 434FS. Annealed 434FS exhibited the widest passivation sweep outputs due to the durability of its passive film compared to untreated and quenched 434FS. An increase in NaCl concentration has a minor effect on the pitting behaviour of the non-treated and 434 steels subjected to heat treatment. Optical images of annealed 434FS exhibited the highest resistance to localized deterioration with fewer corrosion pits compared to untreated and quenched 434FS in the presence of sulphates and chlorides. At the highest chloride concentration, the surface morphology of annealed 434FS showed superficial surface degradation compared to the severe surface degradation exhibited by the untreated and quenched 434FS.